2021
DOI: 10.1093/bib/bbaa379
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive drug repurposing study for COVID19 treatment: novel putative dihydroorotate dehydrogenase inhibitors show association to serotonin–dopamine receptors

Abstract: Dihydroorotate dehydrogenase (DHODH) is a key enzyme required for de novo pyrimidine synthesis and it is suggested as a target for COVID19 treatment due to high pyrimidine demand by the virus replication in the infected host cells as well as its proven effect of blocking of cytokine release by the immune cells to prevent inflammation leading to acute respiratory distress. There are a number of clinical trials underway for COVID19 treatment using DHODH inhibitors; however, there are only a small number of known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 108 publications
2
10
0
Order By: Relevance
“…Similar to reports that drug screening is highly dependent on the chosen cell lines and infection conditions (Mirabelli et al, 2021), 17 of the 24 compounds were shown to inhibit SARS-CoV-2 infection in HeLa-ACE2 cells, including reported compounds with broad-spectrum antiviral activity, such as halofuginone, homoharringtonine, salinomycin sodium salt, ouabain, quinacrine 2HCl, and three kinds of dopamine receptor inhibitors (including trifluoperazine 2HCl, pimozide, and prochlorperazine dimaleate salt) (Chen et al, 2021;Ju et al, 2021;Nemerow and Cooper, 1984;Ochiai et al, 1991;Otręba et al, 2020). Dopamine receptor inhibitors have demonstrated broad-spectrum antiviral activity, including against influenza virus, herpes virus, hepatitis C virus, and SARS-CoV-2 (Berber and Doluca, 2021;Nemerow and Cooper, 1984;Ochiai et al, 1991;Otręba et al, 2020). These broad-spectrum antiviral repurposing candidates are of great significance for the treatment of various emerging viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to reports that drug screening is highly dependent on the chosen cell lines and infection conditions (Mirabelli et al, 2021), 17 of the 24 compounds were shown to inhibit SARS-CoV-2 infection in HeLa-ACE2 cells, including reported compounds with broad-spectrum antiviral activity, such as halofuginone, homoharringtonine, salinomycin sodium salt, ouabain, quinacrine 2HCl, and three kinds of dopamine receptor inhibitors (including trifluoperazine 2HCl, pimozide, and prochlorperazine dimaleate salt) (Chen et al, 2021;Ju et al, 2021;Nemerow and Cooper, 1984;Ochiai et al, 1991;Otręba et al, 2020). Dopamine receptor inhibitors have demonstrated broad-spectrum antiviral activity, including against influenza virus, herpes virus, hepatitis C virus, and SARS-CoV-2 (Berber and Doluca, 2021;Nemerow and Cooper, 1984;Ochiai et al, 1991;Otręba et al, 2020). These broad-spectrum antiviral repurposing candidates are of great significance for the treatment of various emerging viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…CADD has seen broad application in drug discovery against COVID-19. In our collected publications, most of them employed docking screen [37][38][39][40][41][42][43], molecular simulation [44], pharmacophore models [45,46], or machine learning-based virtual screens [47] for drug discovery. Docking screen was the most popular one, which took over 96% of the works.…”
Section: Molecular Docking Is the Most Popular Cadd Methods Against Covid-19mentioning
confidence: 99%
“…It is worth noticing that suggestive evidences propose a role for dopamine in Covid-19 pathophysiology (Attademo and Bernardini, 2021b;Berber and Doluca, 2021;Nataf, 2020b). However, dopaminergic antagonists in ME/CFS would may have sedating effect.…”
Section: Dopaminementioning
confidence: 99%